Confirming existing parameterizations for methane gas transfer velocity in lakes based on direct and high-frequent methods - Esters, Leonie; Rutgersson, Anna; Sahlée, Erik; Kleint, Jan; Gentz, Torben; Wallin, Marcus B.; Iwata, Hiroki; Verlet-Banide, Antonin (Uppsala University, 2022)
Data set for publication 'Gas transfer velocity determination for methane in a temperate lake using direct and high-frequency methods'.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk beskrivning.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Confirming existing parameterizations for methane gas transfer velocity in lakes based on direct and high-frequent methods
Keywords: meteorology; meteorologi; atmospheric sciences; atmosfäriska vetenskaper; geosciences; geovetenskaper; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap